English language acquisition at Islamic boarding school: A systematic review - Wafiroh, Lu'luul; Indah, Rohmani Nur (Universitas Sarjanawiyata Tamansiswa, 2022)
Islamic boarding schools provide various platforms for students to develop their talents in English skills and provide teachers with opportunities to be more active and creative in developing English ideas, such as providing language methods and language programs in Islamic boarding schools. Islamic boarding schools are also a unit that cannot be separated from the reality of society to be able to answer the challenges of the times. How Islamic boarding schools have a significant role in developing student acquisition in second language countries and how the students’ attitudes in Islamic boarding schools affect English language acquisition. This paper aims to find out or compare language acquisition in modern and traditional Islamic boarding schools. Islamic boarding schools cannot be separated from their relationship with society in general. Because the purpose of Islamic boarding schools is to form students, they can enter the community. This study used the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) to conduct this systematic literature review. There are several external and internal factors in mastering foreign languages, especially English, in Islamic boarding schools, starting from the process, environment, participants, target of the language, Islamic values ​​and culture in Islamic boarding schools, and an evaluation of English language acquisition. This study only includes 21 articles regarding English language acquisition at modern Islamic boarding schools in Indonesia; it is hoped that further researchers will explore English language acquisition in several Islamic Boarding schools except Indonesia to review more articles and reach the international area.